Safe Areas for the Placement of Standard Shoulder Arthroscopy Portals: An Anatomical Study - Espinosa Uribe, Abraham G.; Morales Avalos, Rodolfo; Gutiérrez de la O, Jorge; García de León, Oscar R.; Torres García, Jessica Karen; Guzmán Avilán, Katia Denisse; Vílchez Cavazos, José Félix; De la Garza Castro, Oscar; Guzmán López, Santos; Elizondo Omaña, Rodrigo Enrique (2015)
The abundant vascular structures that surround the shoulder joint are complex and variable, complicating arthroscopy approaches. The aim of this study is to determine safe and risky areas around standard posterior and standard anterior portals, and accounting for the distribution of neurovascular structures of small and medium diameters that can lead to intra-articular bleeding during surgery. The standard posterior portal, and standard anterior portal were placed as described in the literature, and punch dissection was performed 2.5 cm around the trocar in situ. The arrangement of each identified structure was photographically documented and digitalized for each anatomic plane; the distance to the trocar and the diameter of each structure were measured. Based on each digitalized anatomic plane, safe and risky tissue areas were determined, and a clock face coordinate system was used to represent these areas. The safe area around the standard posterior portal was located between 11 and 1 o´clock for the left shoulder and 11 and 2 o´clock for the right shoulder. For the standard anterior portal, the safe area was located between 2 and 3 o´clock for the left shoulder and between 9 and 12 o´clock for the right shoulder. However, we did document a risk of injuring the cephalic vein 5 times, the axillary artery 3 times and the deltoid branch of the thoracoacromial artery once. This study reports quantitatively the total number of small diameter structures present in the two shoulder arthroscopic portals evaluated. The safe areas proposed in this study must be evaluated to propose new access points for performing arthroscopic procedures on the shoulder.